Peranan kearifan lokal papadak dalam pengelolaan pesisir dan laut di Desa Nggodimeda dan Desa Siomeda, Kecamatan Rote Tengah - Nelson Chornelius Ketti (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2020)
Nggodimeda and Siomeda Villages utilize coastal and marine resources must be based on rules agreed upon in papadak local wisdom. Customary regulations prohibit and restrict communities from exploiting coastal and marine resources in an environmentally unfriendly manner. The research objective was to explain the application, institutional structure, community participation, the effectiveness of the role of papadak local wisdom in coastal and marine management in the Nggodimeda and Siomeda Villages. Data analysis was carried out by qualitative descriptive analysis. The research was conducted from May to June 2018. The results of the study explained that papadak local wisdom is a social institution established to control community activities that damage the environment and protect marine life. The existence of papadak in Nggodimeda and Siomeda Villages has a clear structure. Community participation makes it easy to enforce established customary rules for coastal and marine management. The existence of papadak customary rules encourages the community to change their habits of activities that were previously destructive to environmentally friendly activities, so that the potential of coastal and marine natural resources in Nggodimeda and Siomeda Villages, Rote Tengah Sub-district are preserved.